In vivo assessment of the active foliar area of banana plants (Musa spp.) using the OTO model - (:unkn) unknown (My University, 2015)
The active foliar area (AFA) is a key parameter in banana crop models, but it is hard to evaluate and existing in vivo assessment models are unreliable. We studied the leaf area dynamics in 405 plantains belonging to nine varieties (Batard, Big Ebanga, CRBP39, D248, D535, Essong, FHIA21, French clair and Mbouroukou n • 3) throughout one crop cycle. An analysis of the structure of 8858 monitored leaf configurations (i.e. each defined by a variety, a number of living leaves and a banana development stage at the monitoring time) revealed the leaf area dynamics versus banana development phases. This analysis also confirmed the relevance of a linear leaf area (LA) increase model. Two ANOVAs were performed to assess the sensitivity of the linear AFA simulation model regarding the variety, number of living leaves and banana development stage at the monitoring time. Finally, we propose a new banana AFA simulation model based on a combination of two linear models. The OTO (for 'leaves One, Three, One') model only involves two input parameters: the number of living leaves at the monitoring time and the length and width of three of these living leaves. The model validation confirmed its independence from the variety, banana configuration at the monitoring time, and cropping conditions. This simple and portable tool can be used to assess the AFA of any banana plant, irrespective of its variety, development stage and cropping conditions.
Keywords: African Research